Peningkatan Kualitas Pendidikan Melalui Penerapan Sistem E-Tracer Study Berdasarkan Kriteria Penilaian Instrumen Akreditasi Program Studi BAN-PT Dan DITJEN BELMAWA KEMENRISTEKDIKTI - Adlina Safitri Helmi; Haswan Haswan (Forum Dosen Indonesia, 2022)
Tracer study implementation primarily aids institutions in their transformation into state universities capable of producing graduates who are adaptable to industrial needs. Universities can use the results of an accurate and structured tracer research as a benchmark for building excellent teaching curricula and education systems. ATI In terms of the preparation of the tracer study questionnaire instrument and technological data collecting, Padang Polytechnic optimizes the implementation of the tracer study. The BAN-PT accreditation assessment criteria and elements, as well as the key questions of the Directorate General of Belmawa, Ministry of Research, Technology and Higher Education's tracer research, were used to create the questionnaire instrument. The collection of data is done in tandem with the building of a website. Identity, type of work, amount of time waiting for graduates to acquire a job, and information about their initial wage were all included in the surveys. According to the results of the alumni search from 2018 to 2020, ATI Padang Polytechnic graduates were absorbed at a rate of 73 percent. The next stage in improving the quality of education for future graduates is to strengthen foreign language proficiency, such as English and Mandarin, as well as soft skills.